Análise do pico de fluxo expiratório antes e após teste de esforço físico submáximo em adultos asmáticos e saudáveis - Silva, Ilkerson Victor Lima da (Brasil, 2025)
Introduction: Asthma is a heterogeneous disease, generally characterized by chronic inflammation of the airways, it is associated with bronchial hyperresponsiveness, causing narrowing of the airways when exposed to a bronchoconstrictor stimulus. Objectives: To compare peak expiratory flow between asthmatic and non-asthmatic adults before and after submaximal exercise testing. Methods: This is a comparative analytical cross-sectional study in which asthmatic and non-asthmatic adults participated in the study, selected for convenience after publicizing the study proposal on social networks and media outlets in the city. Results: The sample consisted of 25 individuals, who were characterized by age, sex, skin color, education, years of study, occupation and monthly family income. Asthmatic individuals have a poor PEF after exertion compared to non-asthmatics, where an average reduction in PEF was observed in the asthmatic group of 151.4 L/min compared to healthy individuals. Discussion: A study carried out in, with a sample of individuals aged 18 to 60 years, compared peak expiratory flow (PEF) at rest between asthmatic and healthy adults, in which the results indicated a significant reduction in PEF in asthmatic individuals compared with healthy people (p= 0.001). Conclusion: it was possible to identify that the PEF in the studied asthmatic population presents a low expiratory flow, caused by the EIB, thus reducing, consequently, its measurement value and its post-exercise recovery time.